338 Feasibility of building a community-based gardening initiative - Sawsan Salah; Lori A. Francis (Journal of Clinical and Translational Science)
Objectives/Goals: Community gardening can foster healthy behaviors among low-income communities. This project aimed to develop a community garden. The primary objectives of this project are (1) assessing the need for and perspective on a community garden at the childcare center, (2) installing the garden, and (3) engaging children in gardening education. Methods/Study Population: This project took place at a childcare center in Harrisburg, PA. Most (74.6%) residents identified as Black or Hispanic/Latino. Every child at the center was eligible for free or reduced lunch. A listening session was held with directly impacted community members to discuss the need for a community garden. Four caregivers, 1 early childhood educator and a master gardener (n = 6) attended the listening session, in which they shared their personal strengths and challenges in growing food. Attendees provided suggestions on what foods they wanted to grow. Children enrolled in the center’s summer program (n = 50) were then invited to participate in weekly gardening activities for 9 weeks. Activities were targeted to preschoolers (3- to 5-year-olds). Older children enrolled in the summer program were welcome to participate. Results/Anticipated Results: Feedback from the listening session was positive. Attendees provided ideas on what to grow and shared interest in expanding the garden to the broader community. Project staff installed four garden beds and planted a variety of herbs (basil, mint, and lavender), fruits (strawberry and melon), and vegetables (tomato, squash, pepper, and onion). Roughly 20–50 children were engaged in the garden each week. Eight weeks into the project, one member from the broader community noticed the garden’s growth and expressed gratitude to the staff, stating “I saw you when you first started planting. This is great what you are doing for the kids.” Children and the center’s staff responded positively to the activities. The staff expressed verbal gratitude for the project and were enthusiastic about maintaining the garden. Discussion/Significance of Impact: Developing a community garden was feasible in this sample and shows potential to (1) increase children’s food literacy and vegetable acceptance and (2) bridge the gap from farm to early childcare education. The project’s success paves way for future gardening initiatives that address food access issues within other diverse low-income populations.